Do trade agreements contribute to the decline in labor share? Evidence from Latin American countries - Martín González Rozada; Hernán Ruffo (Inter-American Development Bank (IDB), 2021)
In this paper, we explore the role of trade in the evolution of labor share in Latin American countries. We use trade agreements with large economies (the United States, the European Union, and China) to capture the effect of sharp changes in trade. In the last two decades, labor share has displayed a negative trend among those countries that signed trade agreements, while in other countries labor share increased, widening the gap by 7 percentage points. We apply synthetic control methods to estimate the average causal impact of trade agreements on labor share. While effects are heterogeneous in our eight case studies, the average impact is negative between 2 to 4 percentage points of GDP four years after the entry into force of the trade agreements. This result is robust to the specification used and to the set of countries in the donor pool. We also find that, after trade agreements, exports of manufactured goods and the share of industry in GDP increase on average, most notably in the case studies where negative effects on labor share are significant. A decomposition shows that all the reduction in labor share is explained by a negative impact on real wages.
Keywords: C01; C1; F1; F16; 330; Labor share; Trade agreements; Synthetic control methods